APPLICATION PROGRAM PAYMENTS THROUGH SCHOOL SAVINGS AT SCHOOL HARAPAN BANGSA BY USING VISUAL BASIC 6.0 - Widya Yuliasti; Ire Puspa W, Ir, MMSI (Jurnal Sistem Informasi, 2005)
In scientific writing, the writer tries to make the payment of application programs inschools through school savings by using Visual Basic 6.0 media. This applicationprogram is expected to help finance part of the recording so that data can be moreaccurate.The author explains the process of making payment applications schools throughschool savings from the stage of registration, deposit, and withdrawals per page.